Peran Harga, Kualitas Produk dan Citra Merek dalam Mendorong Keputusan Pembelian Sabun Pencuci Piring Merek â€œSama Clingâ€ - Masrur Amin; Digitha Oktaviani Putri; Aang Fajar Passa Putra; Ni Made Wiati; Agus Yudi Asmoro (Universitas Merdeka Malang, 2023)
AbstractThe purpose of this study is to ascertain and evaluate how brand image, price, and product quality affect consumers' decisions to buy dishwashing soap under the